(untitled) (Journal of Parents and Teachers, 2026)
As the school year progresses, some parents begin to realise that their child’s performance has dropped; they notice that their child seems a bit lost. They seek to help by arranging private tuition, but often the solution might lie in the environment – in creating the right atmosphere for studying. Here are a few tips to help create a better environment: look after their health, talk to them respectfully, listen patiently, encourage them tirelessly, make sure they get enough sleep, attend school, be patient and patient, avoid comparisons, look after their surroundings, set a timetable, stay on top of things, have a heart-to-heart chat, be careful with the telly, keep in touch with the real world, read and don’t forget the newspaper.